DEFENSIVE STRATEGIES AND FIRM’S RESILIENCE IN A DYNAMIC BUSINESS ENVIRONMENT - Macaulay Enyindah Wegwu (Scholar Express Journal, 2022)
The purpose of this study was to ascertain the relationship between defensive strategies and firm’s resilience in a dynamic environment. The population of this study consisted of 66 senior managers 47 lower managers and 42supervisors selected from manufacturing firms that have been in operation for 5years and above. The probability sampling technique was adopted in the selection of the sample elements. The Krejcie and Morgan table was used to determine the sample size of hundred and thirteen (113) for the study. Data for the study was collected through the distribution of 113 copies of questionnaire to the respondents, out of which 81 copies were returned. All hypotheses were tested and analysed using the Pearson Product Moment Correlation Coefficient. Based on the findings from the study, it was concluded that there is a significant relationship between defensive strategies and firm’s resilience in a competitive business environment. The study therefore recommended that firms should place priority on defensive strategies as means of protecting their firms from potential competitors in order to retain their market share and achieve profitability in a competitive and dynamic economic environment.
Keywords: Defensive Strategy; Pre-Entry Defensive Strategy; Post-Entry Defensive Strategy; firms Resilience